Las normas como herramientas de combate - Paredes Martínez , Roger (2023)
After the implementation of policies for the liberalization of the Peruvian economy in the 1990s, the country experienced a notable increase in its tax collection. This allowed various public works to be carried out, especially by local governments, which generated political gains for various mayors who found growing support among the population. However, this implied the rise of misgivings within the central government, which took advantage of the promulgation of various regulations tending to undermine the collection and financing of local governments, without considering the negative repercussions that they would have on the population, especially among the neediest people.